2021
DOI: 10.21203/rs.3.rs-701286/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activation of Adaptive Immune Cells is an Early Response to Hyperthermic Intraperitoneal Chemotherapy Treatment in Ovarian Cancer

Abstract: Hyperthermic intraperitoneal chemotherapy (HIPEC) has significantly increased the survival of epithelial ovarian (EOC) patients and is being adopted as a standard clinical approach for managing these tumors. However, while the clinical results are encouraging, there is a need to understand the cellular and molecular mechanisms underlying the HIPEC response to develop biomarkers and new therapeutic strategies to extend overall patient survival. We undertook a comprehensive analysis of HIPEC and hyperthermia in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…44,45 Furthermore, these kinds of molecules are detectable in biofluids of cancer patients, so they can be used to reflect the patients' overall status and used for cancer diagnosis and therapeutic monitoring. 45 It has been identified that lncRNA GJA9-MYCBP and PVT1 are aberrantly expressed in different human cancers, [46][47][48] diagnostic biomarker in this kind of cancer. To fill this yawning gap, we investigated the expression of these lncRNAs along with their potential target, MYC, in ALL samples.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Furthermore, these kinds of molecules are detectable in biofluids of cancer patients, so they can be used to reflect the patients' overall status and used for cancer diagnosis and therapeutic monitoring. 45 It has been identified that lncRNA GJA9-MYCBP and PVT1 are aberrantly expressed in different human cancers, [46][47][48] diagnostic biomarker in this kind of cancer. To fill this yawning gap, we investigated the expression of these lncRNAs along with their potential target, MYC, in ALL samples.…”
Section: Discussionmentioning
confidence: 99%